Development of corporate culture at Thaco Group = Phát triển văn hóa doanh nghiệp tại THACO Group - Đỗ, Thị Lan Anh (2020)
The thesis's research objectives include systematizing some basic theoretical issues on corporate culture and development of corporate culture; evaluating the results of developing Thaco Group to be cemented with the Group's development and growth, proposing some possible solutions to successfully develop Thaco Group's corporate culture. By analyzing and comparing the theories with the practice by constituents of organization culture; Analyzing the concerned concepts, phenomenon of objective and non-objective corporate culture; viewpoints and development of corporate culture; evaluating the existing conditions of maintaining and developing the corporate culture at Thaco Group, awareness of achievements and obtained values; Analyzing the shortcomings and its root causes; Analyzing the available characteristics of the unit; accordingly, suggesting the development orientations for the corporate culture, giving out the proper development method and progress, convincing and feasible solutions and recommendations on corporate culture development for the local unit